Microfinance and Conflict: Toward a Conflict-Sensitive Approach - Heen, Stacy (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: In a 1996 report, Geetha Nagarajan remarked that "studies on the consequences of conflicts on the development of financial markets and on issues concerning the design and implementation of financial programmes in post-conflict countries are very limited. In short, issues regarding the development of financial institutions in conflict-affected countries are emerging topics of interest on which there has been little research and even less published." An increasing amount of research on how to do microfinance in post-armed conflict environments has occurred in the ensuing eight years, though little writing links this work to the broader discourse on the development-conflict nexus and the growing international momentum toward conflict-sensitive programming. Moreover, the predominant focus among microfinance researchers is on how conflict impacts microfinance; no writing seems to address how microfinance impacts conflict. This thesis attempts to bridge this gap by proposing three ways in which the mobilization of microcredit could, in itself, dampen conflict tensions and reduce the potential for escalation toward open violence. These three mechanisms, termed "direct", "indirect", and "process" mitigation, evolved out of field research instigated at the request of a small credit union in rural Cameroon to examine the links between credit and conflict. These mechanisms, or typology, form the conceptual heart of this thesis.